The role of copepods in cryo-pelago-benthic coupling in the Weddell Sea, Antarctica - Michels, Jan (Christian-Albrechts-Universität zu Kiel, 2008)
This thesis aimed at investigating the importance of copepods for cryo-pelagic coupling and improving the knowledge on the contribution of copepods to pelago-benthic coupling. Sampling, measurements and experiments were conducted during the two expeditions ANT XXI/2 and ANT XXII/2 with RV “Polarstern” to the shelf of the eastern Weddell Sea in late spring 2003, and to the continental slope of the western Weddell Sea in late spring 2004/2005, respectively. In the western Weddell Sea, the population dynamics and the spatial and temporal variability of (1) the metazoan fauna in the surface and sub-ice layers of a drifting ice floe, and (2) the copepod communities within the ice proper of the drifting floe and of pack ice on a transect from the ice edge to the ice drift station were studied. In the sea ice proper, the harpacticoids Drescheriella spp., mainly naupliar stages, were by far the most abundant species throughout the study (72 - 87 %). Drescheriella spp. and the calanoid Stephos longipes were present in all layers of the ice, whereas the occurrence of the other copepod species was restricted to the lowermost ice layer. The distribution of all species was very patchy and varied greatly between the sampling sites. The metazoan fauna within the sea ice surface layer was dominated by Drescheriella spp. and S. longipes with maximum abundances of 3830 and 1293 ind. L-1, respectively. The populations were mainly comprised of adults and early naupliar stages indicating reproduction of these species within the sea ice surface layer. The copepod abundances were generally higher at the edge of the floe than in the inner part. Drescheriella spp. and S. longipes also occurred regularly in the sub-ice water layer (nauplii, copepodids and adults in Drescheriella spp. and mainly nauplii and adults in S. longipes), however, the dominant sympagic copepod species in this habitat was Ectinosoma sp. with a maximum abundance of 599 ind. m-3. Feeding experiments were conducted with Drescheriella spp. females and copepodids (C) V ...